2017
DOI: 10.3389/fimmu.2017.00526
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Development of Mesenchymal Stem Cells or Their Extracellular Vesicles to Inhibit Autoimmune-Mediated Inflammatory Processes in Systemic Lupus Erythematosus

Abstract: Since being discovered over half a century ago, mesenchymal stem cells (MSCs) have been investigated extensively to characterize their cellular and physiological influences. MSCs have been shown to possess immunosuppressive capacity through inhibiting lymphocyte activation/proliferation and proinflammatory cytokine secretion while simultaneously demonstrating limited allogenic reactivity, which subsequently led to the evaluation of therapeutic feasibility to treat inflammatory diseases. Although regulatory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 62 publications
0
41
0
2
Order By: Relevance
“…However, the trial failed to prolong the therapeutic effects of BMSCs beyond 12 months. In SLE patients, BMSCs are safe and they contribute to improving the SLE Disease Activity Index (SLEDAI) score, blood parameters, and overall survival rate [140][141][142]. JAK/STAT, PTEN/AKT, p53/p21, and Wnt/β-catenin signaling pathways were investigated in mediating BMSC senescence and apoptosis, which might contribute to the development of SLE [143][144][145][146].…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…However, the trial failed to prolong the therapeutic effects of BMSCs beyond 12 months. In SLE patients, BMSCs are safe and they contribute to improving the SLE Disease Activity Index (SLEDAI) score, blood parameters, and overall survival rate [140][141][142]. JAK/STAT, PTEN/AKT, p53/p21, and Wnt/β-catenin signaling pathways were investigated in mediating BMSC senescence and apoptosis, which might contribute to the development of SLE [143][144][145][146].…”
Section: Bmscs Involved In the Treatment Of Immune Disorder Diseasesmentioning
confidence: 99%
“…Recently reports have suggested that extracellular vesicle (EV) secreted from MSCs could be used as a cell-free therapy. The preclinical results showed MSC-derived EVs inhibit inflammatory responses and suppress autoimmune disease pathogenesis [ 131 ]. Most promising animal studies' data and clinical trials about SLE treatment promoted MSC application in the therapy of SLE patients [ 131 ].…”
Section: Msc Clinical Applications In Immune-mediated Diseasementioning
confidence: 99%
“…The preclinical results showed MSC-derived EVs inhibit inflammatory responses and suppress autoimmune disease pathogenesis [ 131 ]. Most promising animal studies' data and clinical trials about SLE treatment promoted MSC application in the therapy of SLE patients [ 131 ]. The Nanjing Drum Tower Hospital in China has used MSCs to treat over 300 refractory SLE patients.…”
Section: Msc Clinical Applications In Immune-mediated Diseasementioning
confidence: 99%
“…Apoptotic MSCs have demonstrated immunosuppressive properties in mouse models of GVHD [38], and extracellular vesicles have improved the symptoms associated with uveitis/uveoretinitis and type I diabetes mellitus [76]. In addition, exosomes have shown success in ameliorating autoimmune conditions including multiple sclerosis [77], Sjögren's syndrome [78], graft versus host disease [59], systemic lupus erythematosus [79], and rheumatoid arthritis [80]. These results suggest the potential use of derivatives for other autoimmune conditions that lack entirely favorable treatment regimens, such as autoimmune pancreatitis.…”
Section: Live Cells Dead Cells and Derivativesmentioning
confidence: 99%